The impact of climate change experience on Palestinian university students’ mental health: a cross-sectional study - Ahmead, Muna; El Sharif, Nuha; Maqboul, Etaf; Zyoud, Raj’a; Nawajah, Inad (Frontiers in Climate, 2025)
IntroductionThe prevalence of severe and catastrophic weather incidents linked to a modified climate system may induce mental problems such as anxiety, depression, distress, and worry in people. This study aims to assess the effect of climate change on depression, anxiety and distress among Palestinian undergraduate students.MethodsThe study utilized a cross-sectional research design. A self-reported questionnaire, including the Climate Change Anxiety Scale, the Hospital Anxiety and Depression Scale (HADS), and the Kessler Psychological Distress cale-6 ere used to gather data.ResultsA total of 1,338 participants were recruited, of whom 66% reported climate change experience and only 6.1% had climate change anxiety. Due to climate change experience, 50.3% of participants had anxiety, 47.5% experienced distress and 36.0% experienced depression symptoms. The multivariate analysis indicated that the likelihood to experience climate change is more pronounced among females (AOR: 0.444, p-value <0.001), participants with high family income (AOR: 0.235, p-value <0.001), and those who perceived climate as impacting their academic performance (AOR: 1.986, p-value <0.001). Also, the participants whose mood was adversely affected by climate change experience (AOR: 2.573, p-value <0.001), participants who reported serious mental health problems (AOR: 2.049, p-value <0.001) and participants experiencing depression were more exposed to climate change experience (AOR: 1.374, p-value: 0.041).ConclusionThe findings indicated that undergraduate students had a low level of climate change anxiety, which may impede their motivation to engage more actively in protecting the environment and high level of depression, distress, stress and anxiety. The university’s engagement in climate change through education, research, and the sharing of information on climate change incidents, mitigation ion and adaptation strategies is essential for improving the mental health of undergraduate students.